(untitled) (Innovative professional education, 2025)
The article considers the issue of creating interactive training manuals for the training of turners in the context of modern trends in vocational education. The use of information and communication technologies (ICT) in the educational process and their impact on improving the quality of specialist training is analyzed. Special attention is paid to changes in the requirements for the profession of turner in the context of the digital transformation of production, as well as the advantages of interactive approaches to learning that contribute to the active involvement of students and more effective mastery of practical skills. The main types of interactive training materials are described: video lessons, simulators, electronic textbooks, and virtual reality programs. The advantages of interactive manuals compared to traditional teaching methods are outlined: the possibility of individualizing the educational process, the availability of materials and practical orientation.